Insider networks - Selman Erol; Michael Junho Lee (Federal Reserve Bank of New York, 2018)
This paper develops a model to study the formation and regulation of information transmission networks. We analyze a cat and mouse game between a regulator, who sets and enforces a regulatory environment, and agents, who form networks to disseminate and share insider information. For any given regulatory environment, agents adapt by forming networks that are sufficiently complex to circumvent prosecution by regulators. We show that regulatory ambiguity arises as an equilibrium phenomenon - regulators deliberately set broad regulatory boundaries in order to avoid explicit gaming by agents. As a response, we show that agents form a core-periphery network, with core members acting as conduits of information on behalf of their stakeholders, effectively intermediating all transmissions of information within the network.
Keywords: D85; G14; G20; 330; network formation; insider trading; regulatory ambiguity; endogenous intermediation